Partially Saturated Bicyclic Heteroaromatics as an sp3‐Enriched Fragment Collection. (6th September 2016) - Twigg, David G.; Kondo, Noriyasu; Mitchell, Sophie L.; Galloway, Warren R. J. D.; Sore, Hannah F.; Madin, Andrew; Spring, David R.
Abstract: Fragment‐based lead generation has proven to be an effective means of identifying high‐quality lead compounds for drug discovery programs. However, the fragment screening sets often used are principally comprised of sp 2 ‐rich aromatic compounds, which limits the structural (and hence biological) diversity of the library. Herein, we describe strategies for the synthesis of a series of partially saturated bicyclic heteroaromatic scaffolds with enhanced sp 3 character. Subsequent derivatization led to a fragment collection featuring regio‐ and stereo‐controlled introduction of substituents on the saturated ring system, often with formation of new stereocenters.